Enhancing electrochemical performance of carbon fiber with lignin for flexible supercapacitors in PVA/H3PO4 matrix - Bianca K. Muñoz; Ilias Serroukh; María Sánchez; Alejandro Ureña (iScience, 2024)
Summary: Lignin is an unlimited resource of an aromatic natural polymer useful for multiple applications, though its use remains limited due to the lack of technology developments. The introduction of lignin as coating of fibers and textile for composites is being recently studied with very promising results. Here, commercial woven carbon fibers (WCFs) have been superficially modified following an easy approach to introduce lignin and carbonize it to enhance the electrochemical performance of the fibers. The modified carbon fibers containing lignin were tested as electrodes using KCl 3 M as electrolyte, reaching 5 F/g at 10 mVs-1. A symmetric supercapacitor was fabricated using these electrodes, and a proof of concept based on a red and yellow light-emitting diode (LED) powered on and a bending test were done. The supercapacitor was able to recover 99% of its capacitance when returned to its original unbent position.